Injection molding additive for 5G optical communication as well as preparation method and application of injection molding additive
By adding a variety of functional auxiliary agents to the polystyrene base resin, a multifunctional additive for 5G optical communication injection molding was prepared, which solved the problem of limited additive functions in the prior art, and achieved efficient dispersion of materials, improved strength and improved signal transmission efficiency.
Patent Information
- Application Number
- CN202411806216.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-07
AI Technical Summary
In the prior art, the additives used for powder injection molding have limited functions and are difficult to meet the requirements of dielectric performance and optical performance in 5G optical communication injection molding process.
Polystyrene is used as the basic resin, and auxiliary agents such as glass fiber, hollow glass microbeads, inorganic nano-scale flame retardants and antioxidants are added to prepare a multifunctional additive by optimizing the formula and separating the mixture.
This additive can not only promote the uniform dispersion and good flowability of the powder, improve the strength and signal transmission efficiency of the material, but also meet the multiple performance requirements of 5G optical communication injection molding materials.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of powder injection molding materials, and specifically relates to an injection molding additive for 5G optical communications, and a preparation method and application thereof. Background Art
[0002] Ceramic powder injection molding (CIM) is a branch of modern powder injection molding (PIM) technology. It can be mass-produced quickly and automatically, and its process can be precisely controlled. Due to the flow filling, the density of the green body is uniform. Due to high-pressure injection, the powder content in the mixture is greatly increased, the shrinkage of the sintered product is reduced, and the product size is precisely controllable and the performance is excellent. It can form complex shapes with transverse holes, inclined holes, concave and convex surfaces, threads, thin walls, and ceramic special-shaped parts that are difficult to cut, etc., and has broad application prospects.
[0003] Powder agglomeration, uniform organization, and fluidity in the powder injection molding process are one of the keys to the success of this technology. In order to improve the dispersibility of the powder in the polymer binder, as well as the uniformity and fluidity of the organizational structure, the above requirements can be achieved by adding additives. In the prior art, the amount of additives used is relatively small, which limits its function. In the 5G optical communication injection molding process, in addition to the above functions, it is also necessary to meet the relevant requirements in terms of dielectric properties and optical properties. Therefore, it is necessary to develop a multifunctional additive that can be used for 5G optical communication injection molding and can improve powder performance. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides an additive for 5G optical communication injection molding, and a preparation method and application thereof. The additive takes polystyrene as the base resin, and optimizes the formula by adding a variety of functional auxiliary agents. The obtained additive is used in the 5G optical communication injection molding process, which can not only promote uniform powder dispersion, good fluidity, and excellent processing performance, but also improve material strength as well as signal transmission efficiency and strength.
[0005] In order to achieve the above object, the present invention provides the following technical solutions: The first object of the present invention is to provide an additive for 5G optical communication injection molding, comprising the following raw material components by weight: Polystyrene 80-100 parts; Surfactant 0.1-3 parts; Lubricant 0.1-5 parts; 2-6 parts of glass fiber; 4-8 parts of hollow glass microspheres; 1-3 parts of flame retardant; Antioxidant 0.5-2 parts.
[0006] The invention uses polystyrene with low dielectric constant, high transmission and refractive properties, low loss and excellent processing performance as the basic resin, and then adds glass fiber to enhance the overall strength of the material, which can meet the requirements of high-frequency communication; adding hollow glass microspheres can further reduce the dielectric constant of the material and reduce signal loss; adding inorganic nano-scale flame retardants not only has a good flame retardant effect, but also can improve the electrical properties and weather resistance of the material, and at the same time can also improve the dispersion performance of the material; adding antioxidants can prevent the material from oxidative degradation and extend the service life of the material; adding surfactants and lubricants can improve the stability of the material, improve the processing performance, and improve production efficiency.
[0007] Furthermore, in the above technical solution, the surfactant is one or more of stearic acid, oleic acid, and behenic acid.
[0008] Furthermore, in the above technical solution, the lubricant is at least one of paraffin wax and polyethylene wax.
[0009] Furthermore, in the above technical solution, the glass fiber is a mixture of glass fibers with a length of 5-10 μm and glass fibers with a length of 5-20 mm in a mass ratio of 3-5:1. In this technical solution, two glass fibers of different sizes are selected to effectively overcome the problems of poor strength and heat resistance of short glass fibers alone and poor dispersibility of long glass fibers alone.
[0010] Furthermore, in the above technical solution, the particle size of the hollow glass microspheres is 10-50 μm.
[0011] Furthermore, in the above technical solution, the flame retardant is nano aluminum hydroxide; the antioxidant is 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxybenzyl)benzene (antioxidant 1330). Nano aluminum hydroxide is an ultrafine aluminum hydroxide and a special flame retardant. It not only has a good flame retardant effect, but also can improve the electrical properties and weather resistance of the material, and can be used in the field of 5G optical communications.
[0012] The second object of the present invention is to provide a method for preparing the above-mentioned 5G optical communication injection molding additive, comprising the following steps: (1) Weigh the raw materials according to the proportions and set aside; (2) First, add the large-sized glass fiber and the surfactant into a high-speed mixer and mix them evenly. Then, add polystyrene, lubricant, and antioxidant and continue to mix at high speed for 10-20 minutes. Then, add half of the small-sized glass fiber, hollow glass microspheres, and flame retardant and continue to mix at high speed for 10-20 minutes to obtain a mixture. (3) The mixed material is fed into a twin-screw extruder through a main feed hopper, and the remaining small-sized glass fibers are fed from a side feed hopper, and the mixture is melt-extruded and granulated to obtain an additive.
[0013] Furthermore, in step (3) of the above technical solution, the melting temperature is 240-270°C and the screw speed is 300-500rpm.
[0014] The present invention also provides an application of an additive for 5G optical communication injection molding. When in use, the additive is first heated to form an additive pre-dissolved material, and then mixed with ceramic powder in a ratio of 18%-25%:85%-82%, and then kneaded at a temperature of 150-190°C for 60-120 minutes, and then granulated at 140°C with a granulator, and injection molded to obtain a special material for 5G optical communication.
[0015] Furthermore, in the above technical solution, the ceramic powder is a mixture of zirconium oxide, aluminum oxide or other ceramic materials; the injection molding temperature is 140-190° C. and the pressure is 25-55 MPa.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention uses polystyrene as the base resin, optimizes the formula, and adds glass fiber to enhance the overall strength and heat resistance of the material; adding hollow glass microspheres can further reduce the dielectric constant of the material and reduce signal loss; adding inorganic nano-scale flame retardants has a good flame retardant effect and can also improve the electrical properties and weather resistance of the material; adding antioxidants can prevent oxidative degradation of the material and extend the service life of the material; adding surfactants and lubricants can improve the stability of the material, improve processing performance, and improve production efficiency.
[0017] The present invention adopts the method of mixing separately and adding glass fiber in sections, which not only has good dispersibility and uniform mixing, but also improves the stability of the material, optimizes the preparation process, and improves the overall performance of the material. The additive used in the 5G optical communication injection molding process can not only promote uniform powder dispersion, good fluidity, and excellent processing performance, but also improve signal transmission efficiency and strength. DETAILED DESCRIPTION
[0018] The experimental methods in the following examples are conventional methods unless otherwise specified. The raw materials involved in the following examples are common commercial products and can be purchased from the market unless otherwise specified.
[0019] The above-mentioned technical features of the present invention and the technical features specifically described below (such as embodiments) can be combined with each other to form a new or preferred technical solution.
[0020] The raw materials involved in the embodiments of the present invention are either existing commercially available products or can be prepared according to existing methods, and the testing methods are industry methods.
[0021] Example 1 An additive for 5G optical communication injection molding, comprising the following raw material components by weight: Polystyrene 80 parts; 0.5 parts of stearic acid; Paraffin 0.1 part; 3 parts of glass fiber; 5 parts of hollow glass microspheres; 2 parts of nano aluminum hydroxide; Antioxidant 1330 0.5 parts; The glass fiber is composed of glass fiber with a length of 5-10 μm and glass fiber with a length of 5-20 mm in a mass ratio of 3:1; the particle size of the hollow glass microsphere is 10-50 μm; The preparation method comprises the following steps: (1) Weigh the raw materials according to the proportions and set aside; (2) Add large-sized glass fibers and surfactants to a high-speed mixer and mix them evenly. Then add polystyrene, lubricant, and antioxidant and continue to mix at high speed for 10 minutes. Then add half of the small-sized glass fibers, hollow glass microspheres, and flame retardant and continue to mix at high speed for 20 minutes to obtain a mixture. (3) The mixed material is added into a twin-screw extruder through a main feeding hopper, and the remaining small-sized glass fibers are added from a side feeding hopper. The mixed material is melted at 250° C. and extruded and granulated at a screw speed of 500 rpm to obtain an additive.
[0022] Example 2 An additive for 5G optical communication injection molding, comprising the following raw material components by weight: Polystyrene 90 parts; 2 parts of oleic acid; 2 parts of polyethylene wax; 2 parts of glass fiber; 8 parts of hollow glass microspheres; 1 part of nano aluminum hydroxide; Antioxidant 1330 1 part; The glass fiber is composed of glass fiber with a length of 5-10 μm and glass fiber with a length of 5-20 mm in a mass ratio of 5:1; the particle size of the hollow glass microsphere is 10-50 μm; The preparation method comprises the following steps: (1) Weigh the raw materials according to the proportions and set aside; (2) Add large-sized glass fibers and surfactants to a high-speed mixer and mix them evenly. Then add polystyrene, lubricant, and antioxidant and continue to mix at high speed for 15 minutes. Then add half of the small-sized glass fibers, hollow glass microspheres, and flame retardant and continue to mix at high speed for 15 minutes to obtain a mixture. (3) The mixed material is added into a twin-screw extruder through a main feeding hopper, and the remaining small-sized glass fibers are added from a side feeding hopper. The mixed material is melted at 260° C. and extruded and granulated at a screw speed of 400 rpm to obtain an additive.
[0023] Example 3 An additive for 5G optical communication injection molding, comprising the following raw material components by weight: Polystyrene 100 parts; 3 parts of behenic acid; 4 parts paraffin; 6 parts of glass fiber; 4 parts of hollow glass microspheres; 3 parts of nano aluminum hydroxide; 2 parts of antioxidant 1330; The glass fiber is composed of glass fiber with a length of 5-10 μm and glass fiber with a length of 5-20 mm in a mass ratio of 4:1; the particle size of the hollow glass microsphere is 10-50 μm; The preparation method comprises the following steps: (1) Weigh the raw materials according to the proportions and set aside; (2) Add large-sized glass fibers and surfactants to a high-speed mixer and mix them evenly. Then add polystyrene, lubricant, and antioxidant and continue to mix at high speed for 20 minutes. Then add half of the small-sized glass fibers, hollow glass microspheres, and flame retardant and continue to mix at high speed for 10 minutes to obtain a mixture. (3) The mixed material is added into a twin-screw extruder through a main feeding hopper, and the remaining small-sized glass fibers are added from a side feeding hopper. The mixed material is melted at 270° C. and extruded and granulated at a screw speed of 300 rpm to obtain an additive.
[0024] Comparative Example 1 An injection molding additive for 5G optical communication, which differs from Example 1 in that the glass fiber is a single length of 5-10 μm glass fiber and the preparation method is the same.
[0025] Comparative Example 2 An injection molding additive for 5G optical communications, which differs from Example 1 in that the glass fiber is a single length of 5-20 mm glass fiber, and the preparation method is the same.
[0026] Comparative Example 3 An injection molding additive for 5G optical communications, which differs from Example 1 in that hollow glass microspheres are not added, and the preparation method is the same.
[0027] Comparative Example 4 An additive for 5G optical communication injection molding, which is different from Example 1 in that the preparation method is as follows: (1) Weigh the raw materials according to the proportions and set aside; (2) adding polystyrene, surfactant, lubricant, glass fiber, hollow glass microspheres, flame retardant, and antioxidant into a high-speed mixer and mixing for 30 minutes to obtain a mixture; (3) The mixed material is added into a twin-screw extruder through a main feeding hopper, melted at 250°C and extruded at a screw speed of 500 rpm to obtain the additive.
[0028] Test example The additives prepared in Examples 1-3 and Comparative Examples 1-4 were used in the 5G optical communication injection molding process, and the method was as follows: the additives were first heated to form an additive pre-dissolve, and then mixed with zirconium oxide ceramic powder in a ratio of 20%:80%, and then mixed at a temperature of 170°C for 100 minutes, and then granulated at 140°C with a granulator, and injection molded when the temperature was raised to 160°C and the pressure was 40MPa to obtain a 5G optical communication special material. The mechanical properties, electrical properties, etc. of the obtained material were then tested, and the results are shown in Table 1.
[0029] Table 1 Performance results
[0030] It can be seen from the results in Table 1 that the additives obtained by the formula and preparation method of the present invention can effectively improve the impact strength and mechanical properties of ceramic injection molding materials. At the same time, it has a low dielectric constant, low loss, and high signal transmission efficiency, which can meet the requirements of 5G optical communication injection molding materials.
[0031] In Comparative Examples 1 and 2, glass fibers of a single size are used, and either the strength does not meet the requirements or the dispersion is poor, affecting the overall performance; in Comparative Example 3, hollow glass microbeads are not added, and the dielectric constant is high, the loss is large, and the signal transmission efficiency is affected; in Comparative Example 4, the raw materials are directly mixed at high speed at one time and added to the twin-screw extruder at one time, and the dispersion and uniformity are poor, affecting the overall performance.
[0032] Finally, it should be emphasized that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various changes and modifications. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. An additive for 5G optical communication injection molding, characterized in that: By weight, it includes the following raw material components: Polystyrene 80-100 parts; Surfactant 0.1-3 parts; Lubricant 0.1-5 parts; 2-6 parts of glass fiber; 4-8 parts of hollow glass microspheres; 1-3 parts of flame retardant; Antioxidant 0.5-2 parts.
2. The additive for 5G optical communication injection molding according to claim 1, characterized in that: The surfactant is one or more of stearic acid, oleic acid and behenic acid.
3. The additive for 5G optical communication injection molding according to claim 1, characterized in that: The lubricant is at least one of paraffin wax and polyethylene wax.
4. The additive for 5G optical communication injection molding according to claim 1, characterized in that: The glass fibers are a mixture of glass fibers with a length of 5-10 μm and glass fibers with a length of 5-20 mm in a mass ratio of 3-5:
1.
5. The additive for 5G optical communication injection molding according to claim 1, characterized in that: The particle size of the hollow glass microspheres is 10-50 μm.
6. The additive for 5G optical communication injection molding according to claim 1, characterized in that: The flame retardant is nano aluminum hydroxide; the antioxidant is 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxybenzyl)benzene.
7. A method for preparing an additive for 5G optical communication injection molding according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: (1) Weigh the raw materials according to the proportions and set aside; (2) First, add the large-sized glass fiber and the surfactant into a high-speed mixer and mix them evenly. Then, add polystyrene, lubricant, and antioxidant and continue to mix at high speed for 10-20 minutes. Then, add half of the small-sized glass fiber, hollow glass microspheres, and flame retardant and continue to mix at high speed for 10-20 minutes to obtain a mixture. (3) The mixed material is fed into a twin-screw extruder through a main feed hopper, and the remaining small-sized glass fibers are fed from a side feed hopper, and the mixture is melt-extruded and granulated to obtain an additive.
8. The preparation method according to claim 7, characterized in that: In step (3), the melting temperature is 240-270°C and the screw speed is 300-500 rpm.
9. An application of the 5G optical communication injection molding additive as claimed in any one of claims 1 to 6, characterized in that: When in use, the additive is first heated to make an additive predissolve, and then mixed with ceramic powder in a ratio of 18%-25%:85%-82%, and then kneaded at a temperature of 150-190°C for 60-120 minutes, granulated at 140°C with a granulator, and injection molded to obtain special materials for 5G optical communications.
10. The use according to claim 9, characterized in that: The ceramic powder is a mixture of zirconium oxide, aluminum oxide or other ceramic materials; the injection molding temperature is 140-190° C. and the pressure is 25-55 MPa.